Faktor yang mempengaruhi pergantian auditor pada perusahaan yang terdaftar di BEI - Harsono, Budi; Rina, Rina (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
This research is able to provide a purpose for conducting analysis and assessment related to the effect of restatement of financial statements, corporate governance, audit company size and replacement of the main director on the change of auditors listed on the IDX in the 2017-2021 period. The data collected as the sample for this study were 1,461 data taken from companies listed on the Indonesia Stock Exchange from 2017 to 2021. The results of this study are certainly able to prove that restatement of financial statements and replacement of the main director have a significant positive effect on auditor turnover compared to governance. company and the size of the audit firm are certainly not able to give an effect on auditor turnover.